Efek Kombinasi Terapi Buerger Allen Exercise dan Senam Kaki Diabetes terhadap Ankle Brachial Index Penderita Diabetes - Hendri Heriyanto; Septiyanti Septiyanti; Rina Delfina (Universitas Faletehan, 2024)
Measuring foot sensitivity with the Ankle Brachial Index (ABI) can be used to identify peripheral sensitivity disorders in patients with diabetes mellitus. Poorly managed peripheral sensitivity disorders can lead to various complications, including foot amputation. Buerger Allen Exercise (BAE) and diabetic foot exercises were proved to give good effects on ABI. However, there were no studies which combine both exercises yet. This study aimed to determine the impacts of the combination of BAE therapy and diabetic foot exercises on the increase of ABI value of diabetic patients. This study used a quasi-experimental approach with pre-test and post-test. The sampling technique was purposive with the total size of 57 respondents, including 19 individuals in the BAE and foot exercise intervention group, 19 individuals in BAE group (control 1), and 19 individuals in foot exercises group (control 2). The analysis results indicated a significant difference between the intervention group’s ABI value and both control gorups (p-value 0.001). This study noted that diabetic patients at Sawah Lebar Public Health Center in Bengkulu City had a higher ABI value when BAE therapy and diabetic foot exercises were combined.